Grid Computing Versus Cloud Computing Concepts from User's Perspectives - Owoc, Mieczysław L.; Hauke, Krzysztof (Advanced Information Technologies for Management – AITM 2009, 2009)
There are natural and attractive trends of data processing improvement and reducing costs in information technologies. Undoubtedly, grid computing as well as cloud computing belong to promising approaches in this respect. In the grid computing concept we find many advantages essential for business as well as for scientific groups that use large scale distributed information. On the other hand, cloud computing offers to different users capability of the usage of services from shared network resources as a global infrastructure. The ultimate aim of this paper is analysis of both concepts in the context from a user's point of view. In the particular sections of the paper common and distinguished properties of the mentioned technologies are presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 191-198